Hicri II. Asır Mısrı: Leys B. Sa’d ve çevresi - Karaman, Dursun (My University, 2015)
HİCRİ İKİNCİ ASIR MISRI: LEYS B. SA’D VE ÇEVRESİ İslam hukukunun teşekkül dönemi içerisinde önemli ilim merkezlerinin yanı sıra Mısır, Şam ve Horasan gibi merkezden uzak çevrelerde de ilmi hareketlilik mevcuttur. Mısır, II. asrın başlarına kadar ilmi anlamda oldukça durağan bir görüntü sergilemektedir. Bununla birlikte özellikle siyasi, dini ve coğrafi şartların etkisiyle Mekke ve Medine’deki ilmi çevrelerle yakın bir bağ kurmuştur. Bu çalışmada hicri II. asır içerisinde yaşamış olan Mısırlı Leys b. Sa’d’ın hayatı ve mensup olduğu ilmi çevre incelenecektir. Tez iki bölümden oluşmaktadır. Birinci bölümde Leys b. Sa’d’ın hayatı, yetişme dönemi, hocaları, talebeleri ve muhtelif yönleriyle ilmi şahsiyeti incelenecektir. Mısırlı hocalarından hareketle II. asra kadar buradaki ilim halkaları zikredilecek ve bu halkalarla Leys’in bağlantısı ortaya konacaktır. Talebelerinden hareketle onun ilmi birikiminin hangi talebeleri sayesinde nerelere ulaştığına dair bilgiler verilecektir. Birinci bölümün sonunda ise Leys, Muhaddis, mutasavvıf, dilcilik ve tarihçilik yönleriyle ele alınacaktır. İkinci bölümde onun fıkhî yönü irdelenecek; yaşadığı dönemde cereyan eden amel tartışmaları içerisinde özellikle İmam Malik’le mektuplaşmaları değerlendirilip, Leys’in fıkıh düşüncesine dair yorumlar irdelenecektir. Sonrasında Leys’in furû fıkha dair görüşlerinin hilâf kitaplarına aktarılması ve cumhurdan ayrıldığı fıkhî görüşeri ortaya konacaktır. Tezin sonunda ise Leys’in görüşlerinin takip edilmesi ele alınıp onun fıkhının bir mezhebe dönüşememesine dair yorumlar ele alınacaktır. slam Hukuk Tarihi, Leys b. Sa’d, Teşekkül Dönemi

EGYPT IN THE SECCOND CENTURY OF HICRA: LAYTH B. SA’D AND HIS ENVIRONMENT During the formation of Islamic Law, there have been other knowledge activities far away then centers of knowledge like Damascus and Khorasan. Egypt has been shown very static activities until the beginning of the II. century of hicra. With all of this, Egypt made a contact with Mecca and Madinah with due to the political, religious and geographical conditions. In this framework, life and scientific environment of Egyptian Layth b. Sa'd will be examined who livedin II century. The thesis consists in two parts. In first part Layth's life, growing period, teachers, students and knowledge of various aspects of personality will be examined. After that, science circles in the Egypt and the Layth' connection to these circles will be mentioned moving from his Egyptian scholer until the II century. His accumulation of knowledge information will be provided moving from his students. In the end of the first part, warrious aspect of his knowledge as a Muhaddith, sufism, linguistics and historiography will be discussed. In the second part his jurisprudential aspect will be studied. Comments about the jurisprudence will be provided, especially in correspondence with ABSTRACT EGYPT IN THE SECCOND CENTURY OF HICRA: LAYTH B. SA’D AND HIS ENVIRONMENT During the formation of Islamic Law, there have been other knowledge activities far away then centers of knowledge like Damascus and Khorasan. Egypt has been shown very static activities until the beginning of the II. century of hicra. With all of this, Egypt made a contact with Mecca and Madinah with due to the political, religious and geographical conditions. In this framework, life and scientific environment of Egyptian Layth b. Sa'd will be examined who livedin II century. The thesis consists in two parts. In first part Layth's life, growing period, teachers, students and knowledge of various aspects of personality will be examined. After that, science circles in the Egypt and the Layth' connection to these circles will be mentioned moving from his Egyptian scholer until the II century. His accumulation of knowledge information will be provided moving from his students. In the end of the first part, warrious aspect of his knowledge as a Muhaddith, sufism, linguistics and historiography will be discussed. In the second part his jurisprudential aspect will be studied. Comments about the jurisprudence will be provided, especially in correspondence with the letters of Imam Malik. In the end of thesis, the follow of the opinions of Layth and that failure to become a school of law will be examined. story of Islamic Law, Layth b. Sa’d, Formation of Islamic Law
Keywords: Hukuk; İslam; Tarih